Menelusuri jejak Melayu-Minangkabau - Bakry, Sastri Yunizarti , 1958-; Kasih, Media Sandra , 1964-; Naim, Mochtar (Yayasan Citra Budaya Indonesia, 2002)
Development of linguistics and socioculture of Malay Minangkabau people in Indonesia; papers of a seminar